Newtonian boreal forest ecology: The Scots pine ecosystem as an example - Hari, Pertti; Aakala, Tuomas; Aalto, Juho; Bäck, Jaana; Hollmén, Jaakko; Jõgiste, Kalev; Koupaei, Kourosh Kabiri; Kähkönen, Mika A.; Korpela, Mikko; Kulmala, Liisa; Nikinmaa, Eero; Pumpanen, Jukka; et al. (PloS one, 2017)
Isaac Newton's approach to developing theories in his book Principia Mathematica proceeds in four steps. First, he defines various concepts, second, he formulates axioms utilising the concepts, third, he mathematically analyses the behaviour of the system defined by the concepts and axioms obtaining predictions and fourth, he tests the predictions with measurements. In this study, we formulated our theory of boreal forest ecosystems, called NewtonForest, following the four steps introduced by Newton. The forest ecosystem is a complicated entity and hence we needed altogether 27 concepts to describe the material and energy flows in the metabolism of trees, ground vegetation and microbes in the soil, and to describe the regularities in tree structure. Thirtyfour axioms described the most important features in the behaviour of the forest ecosystem. We utilised numerical simulations in the analysis of the behaviour of the system resulting in clear predictions that could be tested with field data. We collected retrospective time series of diameters and heights for test material from 6 stands in southern Finland and five stands in Estonia. The numerical simulations succeeded to predict the measured diameters and heights, providing clear corroboration with our theory.